Action observation treatment may improve daily living activities and verb recovery in Parkinson’s disease-dementia: findings from a preliminary randomized controlled trial - Lucia Paciaroni; Elena Mastrosanti; Leonardo Biscetti; Susy Paolini; Sara Mauri; Paolo Fabbietti; Giovanni Renato Riccardi; Marco Bruno Luigi Rocchi; Giuseppe Pelliccioni (Frontiers in Aging Neuroscience, 2024)
Background and objectivesAction observation treatment (AOT) is a novel rehabilitation approach aimed to the recovery of both motor and linguistic deficits in subjects with brain lesions. The aim of the present randomized controlled study was to assess the benefits of AOT treatment in the activities of daily living (ADLs) and in the linguistic abilities of the patients with Parkinson’s disease dementia (PDD) at mild–moderate stage (Hoehn & Yahr’s stage scale: 2–3).MethodsTwenty patients were enrolled and randomly assigned to an experimental group (submitted to AOT) or to a control group. The experimental group (AOT-group) underwent the vision of a video containing 6 complex ADLs, while the control group (C-group) was subjected to a video-clip regarding semantic information of a geographical-naturalistic type without motor content. The treatment duration was 4 weeks. All patients underwent assessment before and after the treatment by the following tools: Unified Parkinson’s Disease Rating Scale Part III (UPDRS-Part III), Alzheimer’s Disease Cooperative Study-Activities of Daily Living Scale (ADCS-ADL), Direct Assessment of Functional Status (DAFS) and subtest Verb Naming of Analysis of Aphasic Deficit Battery (BADA). Paired samples t test was performed to compare all the variables of interest in the time, dividing by groups. p-value<0.05 was considered significant in all analyses.ResultsAOT-group showed an improvement from baseline to the end of study in ADCS-ADL (p = 0.001), BADA (p = 0.011) and DAFS (p = 0.005), while C-group did not change significantly in the time.ConclusionThese preliminary results suggest the potential efficacy of AOT in rehabilitation of ADLs and verb retrieval in people with PD. Further studies will be necessary to verify these findings.